2024
DOI: 10.1021/acsami.3c16822
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-Functionalized Strontium Alginate/Hydroxyapatite Composite Microhydrogel Loaded with Vascular Endothelial Growth Factor Promotes Bone Formation and Angiogenesis

Shi Chen,
Dawei Cheng,
Weimin Bao
et al.

Abstract: Critical-size bone defects are a common and intractable clinical problem that typically requires filling in with surgical implants to facilitate bone regeneration. Considering the limitations of autologous bone and allogeneic bone in clinical applications, such as secondary damage or immunogenicity, injectable microhydrogels with osteogenic and angiogenic effects have received considerable attention. Herein, polydopamine (PDA)-functionalized strontium alginate/nanohydroxyapatite (Sr-Alg/nHA) composite microhyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Furthermore, the composition of nano-hydroxyapatite can be customized to meet various requirements, thereby broadening its potential applications in bone tissue engineering [ 35 , 43 , 46 ]. For instance, Cheng and coworkers discovered that the functionalization of nano-hydroxyapatite with Sr 2+ significantly promoted osteogenesis and angiogenesis through a process of slow release [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the composition of nano-hydroxyapatite can be customized to meet various requirements, thereby broadening its potential applications in bone tissue engineering [ 35 , 43 , 46 ]. For instance, Cheng and coworkers discovered that the functionalization of nano-hydroxyapatite with Sr 2+ significantly promoted osteogenesis and angiogenesis through a process of slow release [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings were aligned with the EDS scan analyses aforementioned, which showed that the highest percentage of calcium element was detected in the Alg/HA/SIS group. Meanwhile, the incorporation of nano-hydroxyapatite particles had also displayed advantages in elevating alkaline phosphatase levels, where some articles had documented the significant role of nano-hydroxyapatite particles in accelerating bone injury healing [ 22 , 42 ]. Furthermore, the composition of nano-hydroxyapatite can be customized to meet various requirements, thereby broadening its potential applications in bone tissue engineering [ 35 , 43 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation